KENYAMANAN PASIEN PRE OPERASI DI RUANG RAWAT INAP BEDAH MARWAH RSU HAJI SURABAYA - Ilma Rosida Rahmawati; Ika Yuni Widyawati; Laily Hidayati (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Preoperation is a phase when the decision for surgical intervention is made and ends when the patient is sent to the operating theatre. The successful operation is determined by the successfull of preparation, including comfort aspect undergoing surgery. The aim of this study was to identify contributing factors of preoperative patient’s comfort at Marwah Room RS HajiSurabaya.Methods: A cross sectional design was used in this study. The population was all of preoperative patient at Marwah Room. Total sample was 26 respondents, taken with consecutive sampling technique. The independent variables were age, surgical experience, anxiety, family support, and pain. The dependent variable was preoperative comfort. Data were collected used questionnaire and observation. Data were analyzed using Spearmen’s Rho and Chi Square testwith α≤0.05.Result: Result showed that age, anxiety, family support, and pain had significantcorrelation with comfort, with level of significant p=0.000, p=0.000, p=0.015, p=0.036 respectively and coefficient correlation of r=0.769, r=0.832, r=0.473, r=0.414 respectively. Surgical experience also had correlation with comfort (p=0.000; x2=15.367).Discussion: Preoperative comfort has correlation with age, surgical experience, anxiety, family support, and pain. Anxiety has the strongest correlation with comfort. Further studies should identify the correlation of that variables to each context of comfort in Kolcaba’s Theory